A randomized phase III trial of adjuvant chemotherapy versus concurrent chemoradiotherapy for postoperative cervical cancer: Japanese Gynecologic Oncology Group study (JGOG1082). Issue 4 (April 2021) - Furusawa, Akiko; Takekuma, Munetaka; Mori, Keita; Usami, Tomoka; Kondo, Eiji; Nishio, Shin; Nishino, Koji; Miyamoto, Yuichiro; Yoshimura, Ryoichi; Watanabe, Miho; Mikami, Mikio; Enomoto, Takayuki
Abstract : Background : The standard treatment for stage IB‐IIB cervical cancer is radiotherapy or radical hysterectomy; after radical hysterectomy, adjuvant concurrent chemoradiotherapy is recommended for patients with high risk factors. However, adjuvant concurrent chemoradiotherapy can cause severe gastrointestinal and urinary toxicity. Primary Objective : To assess whether postoperative adjuvant chemotherapy is not inferior to adjuvant concurrent chemoradiotherapy for overall survival in patients with high risk cervical cancer. Study Hypothesis : Adjuvant chemotherapy is not inferior to adjuvant concurrent chemoradiotherapy for overall survival and will reduce severe toxicities. Trial Design : Patients with high risk factors after radical hysterectomy will be randomized 1:1 to receive adjuvant concurrent chemoradiotherapy or adjuvant chemotherapy. Treatment will be started within 6 weeks of surgery. The concurrent chemoradiotherapy group will receive whole pelvis irradiation (50.4 Gy) and cisplatin (40 mg/m 2 /week). The chemotherapy group will receive paclitaxel (175 mg/m 2 ) plus cisplatin (50 mg/m 2 ) or carboplatin (AUC=6) every 3 weeks for six cycles. Major Inclusion/Exclusion Criteria : Patients with high risk stage IB‐IIB cervical cancer (squamous cell carcinoma, adenocarcinoma, and adenosquamous cell carcinoma) who underwent radical hysterectomy are eligible for the study. High risk is defined as the presence of pelvic lymph node metastasis and/or parametrial invasion. Primary Endpoint : The primary endpoint is overall survival. Sample Size : 250 patients in total are required. Estimated Dates for Completing Accrual : This study began in November 2019, and 250 patients will be accrued within 5 years. Trial Registration Number : The study has been registered with the Japan Registry of Clinical Trials (jRCTs041190042).